2022
DOI: 10.3390/jcm11061530
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Assessment of Skeletal Muscle Mass and Muscle Quality Using Computed Tomography: Incidence of Sarcopenia in Patients with Intrahepatic Cholangiocarcinoma Selected for Liver Resection

Abstract: Background: Sarcopenia is considered a predictor of poor postoperative and long-term results following liver resection for intrahepatic cholangiocarcinoma (ICC). The aim of our study was to assess the incidence of sarcopenia in patients resected for ICC and its relation to preoperative clinical factors. Methods: Patients resected for ICC in our unit, with available preoperative CT scans within one month before operation, were enrolled in the study. Skeletal muscle index (SMI) and skeletal muscle radiodensity (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…After full-text screening, 25 studies were eliminated either due to non-compliance with inclusion criteria or due to unavailability of data. Ultimately, 33 article ( 21 – 53 ) were included in the meta-analysis ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…After full-text screening, 25 studies were eliminated either due to non-compliance with inclusion criteria or due to unavailability of data. Ultimately, 33 article ( 21 – 53 ) were included in the meta-analysis ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…A previous study found the incidence of sarcopenia among ICC patients following receipt of liver resection to be 50%. Preoperative nutritional evaluation is important for ICC[ 41 ]. In addition, nutritional factors may affect the disease incidence.…”
Section: Discussionmentioning
confidence: 99%
“…Malnutrition negatively affects patient recovery after surgery, increases health care costs, and is associated with shorter survival in cholangiocarcinoma [ 9 , 10 ]. It has been observed that approximately 32% of patients diagnosed with malnutrition at the time of admission for surgery [ [11] , [12] , [13] , [14] ]. Additionally, preoperative malnutrition has been significantly linked to postoperative liver failure and poor surgical outcomes [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%